Coverage and Framing of Emerging STI and STEM by Four Major Nigerian Newspapers and Implications for National Development - Herbert E. Batta; Nnamdi T. Ekeanyanwu; Charles D. Obot; Iniobong C. Nda (European Scientific Journal, ESJ, 2022)
In Nigeria, there is a gross deficit of empirical research on emerging STI content in the media. This study investigated four prominent newspapers in Nigeria to ascertain the extent to which STEM and emerging STI are covered and framed. We posed the following research questions covering reportage, sourcing, framing, and implications. The methodology involved a content/framing analyses of Daily Trust, Leadership, The Guardian and The Punch. A census sampling of 728 newspaper issues was conducted covering a period of six months spanning between December 1, 2020 and May 31, 2021. The results indicate a near zero coverage of emerging STI in the four dailies. Other results show that of the eight areas of STEM examined, medical/health sciences (48%), agricultural sciences (24%) and ICTs/engineering (19%) received more coverage. Earth/environmental sciences, physical and chemical sciences, marine, space, and mathematical sciences were accorded near zero coverage. On sourcing of STEM stories in the four dailies, 54% was sourced in-house by the journalists, 33% came from national STI institutions, while 13% was obtained from foreign and internet sources. On framing, 42% of STEM stories were framed in terms of health, risk, and safety; 39% in economic and political frame, while academic, environmental, ethical and “other frames scored between 7% and below. The conclusion of the study is that newspaper coverage of emerging STI was near zero reflecting and projecting the dismal status of emerging STI in Nigeria while the coverage and framing of STEM depicted the media agenda of concentration on medical, agricultural, and ICT endeavours to the neglect of others.